2007
DOI: 10.1159/000099589
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Profile in Patients with Essential Hyperhidrosis

Abstract: Background/Aims: The main debates on hyperhidrosis are whether there are some personality features such as anxiety or stress, or whether the psychological symptoms are due to negative social feedback from early life. We aimed to investigate the temperament and character dimensions with a psychobiological inventory. Methods: We recruited patients with hyperhidrosis (n = 26) and chronic renal failure (n = 44) as well as healthy subjects (n = 22) from dermatology and nephrology clinics and the general population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Th e Temperament and Character Inventory (TCI) has been commonly used in the research studies involving various areas including neuropsychology, neuroimaging, personality traits, and developmental abnormalities (Karaca et al 2007;Turhan-Haktanir et al 2010;Youn et al 2002). Beyond these, it has been shown that distinct personality domains exist in ASD parents (Austin 2005Bolton et al 1994Micali et al 2004;Murphy et al 2000;Pickles et al 2000;Piven et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e Temperament and Character Inventory (TCI) has been commonly used in the research studies involving various areas including neuropsychology, neuroimaging, personality traits, and developmental abnormalities (Karaca et al 2007;Turhan-Haktanir et al 2010;Youn et al 2002). Beyond these, it has been shown that distinct personality domains exist in ASD parents (Austin 2005Bolton et al 1994Micali et al 2004;Murphy et al 2000;Pickles et al 2000;Piven et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Th e character dimensions appraise the personal diversities in metacognitive processes regulating emotional confl icts vs a person ' s goals and values (Karaca et al 2007). SD implies being independent, skillful, and responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Medications associated with excessive sweating include propranolol, physostigmine, pilocarpine, tricyclic antidepressants, and serotonin reuptake inhibitors. It has been reported that the temperament and character profile of patients with essential hyperhidrosis 16 is not related to social phobia or personality disorder.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The true etiology of this disorder remains unknown. PFH may represent a complex dysfunction of the autonomic nervous system, involving both the sympathetic and parasympathetic pathways [5]. Psychiatric symptoms, such as depression, anxiety and stress have frequently been implicated to play a role in the genesis of the disease as well as in its evolution [6].…”
Section: Introductionmentioning
confidence: 99%